1991
DOI: 10.1007/bf00267079
|View full text |Cite
|
Sign up to set email alerts
|

The tissue distribution of rat chromogranin A-derived peptides: evidence for differential tissue processing from sequence specific antisera

Abstract: The distribution of chromogranin A and related peptides in rat tissues was investigated using sequence specific antisera. N- and C-terminal antisera and a presumptive C-terminal rat pancreastatin antiserum immunostained an extensive neuroendocrine cell population throughout the gastro-entero-pancreatic tract, anterior pituitary, thyroid and all adrenomedullary cells. However, mid- to C-terminal antisera immunostained a subpopulation of chromogranin A positive cells. Most notable of these was with the KELTAE an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
56
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 20 publications
8
56
0
Order By: Relevance
“…Studies have been performed with nine region-specific antibodies to the rat CgA molecule in the rat GI mucosa. Curry et al (1991) found different immunoreactive patterns with their antibodies at various levels of the rat GI tract but did not relate the staining results to the cell type. Norlén et al (1997Norlén et al ( ,2001) reported a similar study but referred their staining results to the different NE cell types in the rat stomach.…”
mentioning
confidence: 84%
“…Studies have been performed with nine region-specific antibodies to the rat CgA molecule in the rat GI mucosa. Curry et al (1991) found different immunoreactive patterns with their antibodies at various levels of the rat GI tract but did not relate the staining results to the cell type. Norlén et al (1997Norlén et al ( ,2001) reported a similar study but referred their staining results to the different NE cell types in the rat stomach.…”
mentioning
confidence: 84%
“…Furthermore, several studies demonstrated that CgA could be degraded in a tissue-specific manner, which led to important disparities in the tissular distribution of the peptides released (Cetin and Grube, 1991;Curry et al, 1991;Watkinson et al, 1991). It is likely that the proteolysis properties may be responsible for the variability of the fragments found in normal and pathological tissues, blood or urine.…”
mentioning
confidence: 99%
“…The single exception is parastatin, the existence of which is inferred from the presence of a 14 kDa C-terminal CGA fragment generated in rat insulinoma cells, and the biological activity of the parastatin fragment generated by endoproteinase Lys-C digestion of purified CGA [88,108] The processing of CGA seems to occur preferentially at some but not all pairs of basic amino acids, and at some single basic amino acids, at the C-and N-termini of the molecule [27,103,110,111]. The extent of chromogranin A processing is highly tissuedependent: processing appears to be least complete in the adrenal medulla and progressively greater in intestine, stomach, peripheral nerves, and pancreas [27,103,[110][111][112]. The endocrine pancreas appears to exhibit the highest level of processing based on the ratio of intact CGA to fully processed /3-granin as well as pancreastatin [21,27,88].…”
mentioning
confidence: 99%